Understanding leadership competencies : creating tomorrow's leaders today - Guggenheimer, Patricia (Crisp Pub. Menlo ParkUS, 1998)
Defines 'competency'. Identifies the 9 leadership competencies that form the Leadership Capstone Model as: passion, humour, courage, integrity and trust, energy/vitality/enthusiasm, building a team, setting priorities, creativity, and vision. Explores each competency and provides exercises for reinforcement, self-evaluation and application. Provides case studies.